Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set: 72

Answer

$(y^{2}+6)(\sqrt 2y-1)(\sqrt 2y+1)$

Work Step by Step

Step 1: Let u=$y^{2}$ $=2u^{2}+11u-6$ Step 2: Factor $2u^{2}+11u-6$ =(u+6)(2u-1) Step 3: Substitute back $u=y^{2}$ $=(y^{2}+6)(2y^{2}-1)$ Step 4: Factor $2y^{2}-1$ $=(\sqrt 2y-1)(\sqrt 2y+1)$ Step 5: Place all of the factors into one $(y^{2}+6)(\sqrt 2y-1)(\sqrt 2y+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.